Retroperitoneal Bleeding: An Experience During Prophylactic Anticoagulation in a Patient With Nephrotic Syndrome. Issue 10 (28th July 2017) - Okada, Mari; Akimoto, Tetsu; Kawamata, Mutsumi; Imai, Toshimi; Hishida, Erika; Kohara, Marina; Miki, Atsushi; Murakami, Takuya; Sugase, Taro; Masuda, Takahiro; Ono, Yuko; Ueda, Yoshihiko; et al.
The association between nephrotic syndrome (NS) and a hypercoagulable state has been demonstrated. Controlling the blood clotting activity may therefore be attractive for patients with nephrosis in terms of thromboembolism prophylaxis. We herein report a 75-year-old woman with minimal change disease who developed pains in the right back, groin, and thigh because of retroperitoneal bleeding during prophylactic anticoagulation with unfractionated heparin. Although this procedure has not been accepted as the standard of care for patients with nephrosis, pharmacologic prophylaxis may already be practiced empirically, as in the present patient. We believe that our experience highlights the pitfalls of such a management in patients with nephrosis, implying the need for a diagnostic strategy for identifying those patients with NS who can benefit from prophylactic anticoagulation. Several concerns that emerged in this case are also discussed.